Protected wading bird species threaten relict centenarian cork oaks in a Mediterranean Biosphere Reserve: A conservation management conflict - García, Luis V.; Ramo, Cristina; Aponte, Cristina; Moreno, Adela; Domínguez, María T.; Gómez-Aparicio, LORENA; Redondo, Ramón; Marañón, Teodoro (Biological Conservation, 2011)
Conservation management conﬂicts frequently arise when an overpopulation of a protected organism has negative effects on other valuable elements in the same ecosystem. We studied the interactions between a colony of protected tree-nesting wading birds and a remnant population of centenarian cork oaks that was part of the formerly dominant forests in the Doñana Biological Reserve (SW Spain). A signiﬁcant increase in the tree mortality rates has been recorded in areas that are yearly inﬂuenced by the bird colony. We analysed a cohort of surviving trees using a gradient of nesting bird inﬂuence. Tree-nesting history, bird isotopic signature (d 15 N), tree health-related parameters (defoliation, d 13 C and leaf surface coverage by faeces) and several soil variables were evaluated. Bird inﬂuence was related to increased soil salinity. This increase correlated to increased water-use efﬁciency for the leaves and to crown defoliation, suggesting that the heavily occupied trees are under higher stress and in poorer health condition than the unoccupied ones. We tested structural equations models (SEM) that were based on hypothesised bird effects on the health of the trees. Soil-mediated effects of the nesting birds best explained the symptoms of the declining health of the trees, whereas the percent of leaves’ surface that was covered by faeces did not improve the ﬁtted SEM model. For the reserve’s managers, a challenging trade-off exists between preserving the relict trees, which have a high genetic diversity and a key ecological role in these savannah-like ecosystems, and maintaining the current nesting area for these protected, but expanding, wading birds.
Keywords: Colonial waterbirds; d13C; d15N; Doñana; Heronry; Indirect effects; Quercus suber; Stable isotopes

Scavenging in Mediterranean ecosystems: effect of the invasive Argentine ant - Angulo, Elena; Caut, Stéphane; Cerdá, Xim (Biological Invasions, 2011)
Above-ground invertebrates may represent a high proportion of animal biomass, but few data are available on their fate after death. In Mediterranean ant communities, they are frequently scavenged by ants. Here, we assessed the consequences of Argentine ant invasion on the removal of arthropod corpses in Don˜ana National Park (SW Spain). In three natural habitats that differed in their degree of vegetation cover (i.e. protection for ants against high temperatures), we experimentally provided dead Drosophila, and observed their disappearance over a 60-min period at different times of day and year. The habitats used were isolated cork oak trees, pine tree forest and dry scrubland; we compared invaded with uninvaded plots in each. Oak trees were the most invaded habitat, while scrubland was the least and the only one where the Argentine ant coexisted with native ant species. In accordance with this degree of invasion, the Argentine ant removed the highest percentage of dead ﬂies in oak trees and the lowest in scrubland. Its performance as scavenger was higher than uninvaded ant communities, but it was reduced at high temperatures, when native species were highly efﬁcient. The saturated distribution of the Argentine ant colony seems to be the key to its efﬁciency. We discuss how the occurrence and scavenger efﬁciency of the Argentine ant could affect the nutrient cycling and the progression of its invasion.
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: á; Ant communities; Arthropod corpses; Doñana; Linepithema humile; linepithema humile á don; Temperature; temperature á ant communities

Plant functional types and ecosystem function in Mediterranean shrubland - Barradas, Díaz; Zunzunegui, M. (Journal of Vegetation Science, 1999)
This study attempts to identify Plant Functional Types (PFTs) within the scrub vegetation of the stabilized sand dunes of the Doñana National Park (southwestern Spain) and to explore possible links with ecosystem function. Two 10-km long transects were sampled along a gradient of water table depth from elevated and dry dunes to a border area close to the salt marsh. A matrix of cover values for 20 woody species × 58 plots and a matrix of 24 morphological and physiological traits × 20 species were analysed by means of DCA and TWINSPAN to identify the main vegetation types and PFTs. In order to know the predominant plant traits, the matrix of 20 species × 58 plots was multiplied by the 24 traits × 20 species matrix. The resulting 24 traits × 58 plots matrix was analysed by means of DCA. The main vegetation types coincide with the previous descriptions of the Park with Juniperus phoenicea woodland and xerophytic species dominating the top of the dunes and hygrophytic species with isolated Quercus suber trees in the depressions. Previous classifications of Mediterranean woody plants resulted in two main PFTs. The present analysis confirmed these two groups: maquis versus garrigue, but added four new groups. The analysis of the traits × plots matrix revealed that the main trend of variation is related to the water table gradient, while the traits related to the species of mature plant communities had little weight in the analysis because these communities are restricted to isolated patches.
Keywords: Doñana; Plant trait; Regeneration; water potential; Water table depth